2010
DOI: 10.1007/s10886-010-9749-7
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of a Diurnal Pattern of Catechin Exudation by Centaurea stoebe

Abstract: The exudation of secondary metabolites at phytotoxic concentrations has been proposed as a mechanism of invasion for some exotic plant species. Catechin is a natural flavanoid implicated in the potential allelopathic interactions of Centaurea stoebe. However, recent studies have shown that catechin is highly unstable and not likely to accumulate in growing medium at phytotoxic concentrations. All previous studies that investigated the allelopathic potential of catechin assumed a continuous exudation of this co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…6 The retracted note conveys that the authors of the original report failed to reproduce catechin secretion and phytotoxicity against Arabidopsis thaliana. In contrast, several other lines of work, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] some originating from the same research group showed catechin secretion to an order of mg g -1 samples. 5,7,14,15,18,20 It is valid to argue that the irreproducibility in catechin secretion observed by Stermitz et al (2009) 6 could be related to the factors such as instability of catechin in medium and sampling time.…”
Section: Catechin Secretion and Phytotoxicitymentioning
confidence: 69%
“…6 The retracted note conveys that the authors of the original report failed to reproduce catechin secretion and phytotoxicity against Arabidopsis thaliana. In contrast, several other lines of work, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] some originating from the same research group showed catechin secretion to an order of mg g -1 samples. 5,7,14,15,18,20 It is valid to argue that the irreproducibility in catechin secretion observed by Stermitz et al (2009) 6 could be related to the factors such as instability of catechin in medium and sampling time.…”
Section: Catechin Secretion and Phytotoxicitymentioning
confidence: 69%
“…In addition, several laboratories including the Vivanco lab had difficulty re-isolating catechin from the root exudates of spotted knapweed plants grown in vitro. Recently, the riddle has been partially solved; a third party laboratory discovered that spotted knapweed roots release catechin during the day and that this compound decreases its concentration in the exudates through the night (Tharayil and Triebwasser, 2010). The reason for this cyclic secretion has not been unraveled but it resembles the situation that we uncovered in the field.…”
Section: Introductionmentioning
confidence: 89%
“…One of the most studied has been catechin, a flavonoid present in the root exudates of the invasive spotted knapweeds Centaurea maculosa and Centaurea stoebe, which exhibits a strong inhibitory effect on a number of plant species Weir et al, 2003;Tharayil and Triebwasser, 2010). It has been found that the concentration and effect of this compound increase in response to light intensity (Tharayil and Triebwasser, 2010). This resolves, in part, the question of why the concentration and the allelopathic effect of catechin change under different conditions (Perry et al, 2007).…”
Section: Root Secretion Of Invasive Species Increases Crop Lossesmentioning
confidence: 99%
“…Perry et al (2007) found that the concentration of catechin was higher during the months of May to August, when there are more hours of light. Although the molecular mechanism by which this is achieved is unknown, it has been proposed that light regulates flavonoid biosynthesis and, therefore, catechin accumulation (Tharayil and Triebwasser, 2010;Hong et al, 2014).…”
Section: Root Secretion Of Invasive Species Increases Crop Lossesmentioning
confidence: 99%